Successful treatment of rituximab-unresponsive elderly-onset neuromyelitis optica spectrum disorder and hypogammaglobulinemia with ofatumumab plus intravenous immunoglobulin therapy in a patient with mutant FCGR3A genotype: A case report - Zhang, Weihe; Jiao, Yujuan; Jiao, Jinsong; Jin, Ming; Peng, Dantao (Frontiers in Immunology, 2022)
Background Elderly-onset neuromyelitis optica spectrum disorder (NMOSD) is a rare entity that poses a therapeutic challenge. We report a case of elderly-onset NMOSD with mutant FCGR3A genotype who was successfully treated with ofatumumab after multiple episodes of relapse. Case Report The patient was a 67-year-old woman who was diagnosed with NMOSD with high disease activity. She experienced six episodes of relapse over a period of 2 years despite immunosuppressant therapy with intravenous rituximab (RTX), oral steroids, mycophenolate mofetil, and tacrolimus. At the last relapse, she was unable to walk and developed immunosuppressant-induced hypogammaglobulinemia. Based on the insufficient B cell depletion and FCGR3A-FF genotype carrier, the patient was diagnosed as RTX non-responder. After subcutaneous ofatumumab plus intravenous immunoglobulin replacement therapy, she was able to walk independently, and experienced no further relapse. Ofatumumab was well-tolerated, and sufficiently depleted the circulating B cells. Conclusion Ofatumumab might be an effective alternative in RTX-unresponsive NMOSD, and seems to be safe in elderly patients.